Paradigma Dakwah Kultural: Infiltrasi Nilai Ketahuidan melalui Kontruksi Karakter Puntadewa - Sucipto, Sucipto; Hidayatullah, Ahmad (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2024)
Spreading Islam in the early Walisongo period amidst the strong establishment of the Hindu monarchy - Majapahit - was certainly not an easy thing. Adaptation and persuasion efforts were needed so that Islamic values did not encounter resistance from Javanese society at that time. One of the things that Walisongo - especially Sunan Kalijaga - did was infiltrate it through arts and culture. One of the things he did was construct a wayang character, namely Puntadewa, which incidentally was very popular with the people of his time.Using qualitative research with library research specifications, the author tries to explore how the value of monotheism is infiltrated into society through the construction of Puntadewa's character. The results of this research can be concluded that Puntadewa's position as the eldest of the Pandavas was used as an initial benchmark in infiltrating the value of monotheism into Javanese society at that time. The protagonist's typical character traits, which from the start are filled with attributes of perfection, make this step quite smooth. A series of storylines attempted in such a way as to reduce the previous values attached to the Mahabharata epic - and some of which were contrary to Islam - were actually quite successful and even without physical resistance in society at that time.